Transient expression of plant specific domain of potato aspartic proteases (Stap-Psi) restricts P. Infestans spread in potato leaves - Frey, María Eugenia (2016)
Plant specific insert (PSI) is a domain present in the precursors and mature atypical plant aspartic proteases (APs). Several plant APs have been associated with the plant mechanism of defence against pathogens. However, only two (StAP1 and StAP3, for Solanum tuberosum APs) of these proteases, contain the PSI domain into the mature form. We have previously reported the cytotoxic activity of the recombinant StAP-PSI towards plant pathogens. However the role of PSI domain of StAPs in the plant mechanism defense is still unknown. The aim of this work was to analyze the effect of transient expression of StAP-PSI in potato leaves infected by P. infestans. Results obtained show that StAP-PSI expression reduces the P. infestans affected area in a 60 % compared with the control ones. Analysis by qPCR shows an increase of the transcript level of the hypersensitive response marker (hsr203J) in potato leaves that express StAP-PSI, independent of the P. infestans infection; however the highest increase of this gene was detected in leaves at 6 h. after infection. Additionally, an increase of the WRKI1 transcript level was detected in potato leaves that express StAP-PSI. Results obtained here indicate that, PSI domain of StAPs could have a direct (as antimicrobial compound) and indirect (as an inductor molecule) role in the plant mechanism to restrict the pathogen spread.